Vascular plant diversity and carbon stocks of selected sacred groves in Southwestern, Nigeria (2025)
Sacred groves are hotspot areas for tree species diversity and rare woody plants. Tree species composition have not been evaluated for its contribution to carbon in sacred groves. This study was designed to investigate influence of stand structure on variation of biomass and soil carbon stocks in the selected sacred sites in Southwestern, Nigeria. Ten (0.09ha) plots were randomly demarcated in each sacred grove. Tree ≥5cm Diameter-at-Breast Height (DBH) were identified and species diversity indices (Shannon-Weinner, H´; Simpson, 1-D) were computed. Total height (TH) and DBH were measured for volume and carbon estimation. Soil samples were collected with cores at three depths in each plot. Core samples were oven-dried at 105°C and 100g of soil was separated into >2.0, 2.0-1.0, 1.0-0.5, 0.5-0.05 and <0.05mm aggregates and carbon proportion determined. Data were analysed using descriptive statistics and ANOVA. A total of 28 tree species representing 18 families, 23 tree species representing 14 families, 8 tree species representing 6 families and 16 tree species representing 12 families were identified in Ori-Oke, Bilikisu-Sugbo, Olumo rock and Osun-Osogbo groves, respectively. The H´ ranged from 2.61 (Ori-Oke) to 1.67 (Olumo-rock), while 1-D ranged from 0.94 (Bilikisu) to 0.74 (Olumo-rock). Biomass carbon ranged from 24240.00 (Bilikisu-Sugbo) to 7998.36 kg/ha (Ori-Oke). Carbon content increased with decrease in aggregate size in soil depths of Ori-Oke and Bilikisu-Sugbo while decreased with decrease in Olumo-Rock and Osun-Osogbo Groves. Bilikisu-Sugbo obtained the highest tree species diversity and carbon storage. Therefore, Bilikisu-Sugbo should be considered for plant diversity and carbon storage conservation schemes.